2022
DOI: 10.3390/v14020325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 Evolution in Paediatric Primary Airway Epithelial Cell Cultures Compared with Vero-Derived Cell Lines

Abstract: SARS-CoV-2 can efficiently infect both children and adults, albeit with morbidity and mortality positively associated with increasing host age and presence of co-morbidities. SARS-CoV-2 continues to adapt to the human population, resulting in several variants of concern (VOC) with novel properties, such as Alpha and Delta. However, factors driving SARS-CoV-2 fitness and evolution in paediatric cohorts remain poorly explored. Here, we provide evidence that both viral and host factors co-operate to shape SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The potential evolutionary drivers of NTD variation are further informed by our independent experiments with authentic SARS‐CoV‐2. Serial passage in Vero E6 cells selects for SARS‐CoV‐2 with a deletion of the polybasic cleavage site (ΔPBCS, Davidson et al , 2020 ; Bamford et al , 2022 ). In our studies in this background, further passage led to the emergence of a virus with spontaneous deletion of the entire N2 loop (Δ67–76, Fig 4E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential evolutionary drivers of NTD variation are further informed by our independent experiments with authentic SARS‐CoV‐2. Serial passage in Vero E6 cells selects for SARS‐CoV‐2 with a deletion of the polybasic cleavage site (ΔPBCS, Davidson et al , 2020 ; Bamford et al , 2022 ). In our studies in this background, further passage led to the emergence of a virus with spontaneous deletion of the entire N2 loop (Δ67–76, Fig 4E ).…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by the emergence of NTD loop variants in other cell culture experiments (Shiliaev et al , 2021 ). Importantly, we have previously demonstrated that the passage of SARS‐CoV‐2 in Vero E6 cells, and the emergence of ΔPBCS viruses, results in attenuated replication in primary human airway cells (Bamford et al , 2022 ). Therefore, whilst the viruses characterised here possess altered replication in monkey‐derived Vero E6 cells, there is no reason to expect enhanced replication in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDCK, cells for IAV, (ii) Vero cells for EMCV, and (iii) VAT cells, i.e. VeroE6 cells expressing human ACE2 and TMPRSS2, for SARS2 [ 35 , 36 ]. Dulbecco's modified Eagle's Medium (DMEM,) with 10% v /v Foetal calf serum (FCS) with penicillin and streptomycin (1% v / v ), was used for all routine cell and virus cultures, except FCS was omitted for work with PR8 and, replaced instead with 0.3 wt% bovine serum albumin (BSA) and TPCK (L-1-tosylamido-2-phenylethyl chloromethyl ketone)-treated trypsin (1 μg/mL), to facilitate multi-cycle infection.…”
Section: Methodsmentioning
confidence: 99%
“…This virus-containing solution was then used to assess the level of viral infectivity remaining on the sample. Virus infectivity was determined by TCID 50 measurements in 96 well plates (IAV and EMCV) [ 40 ], or by plaque assay in 24 well plates (SARS2) using a method described elsewhere [ 36 ], except modified using VAT cells and incubating infections for 48 h prior to determining the number of plaque forming units, PFU, produced. Calculated virus infectivity values were based on visual viral cytopathic effect measurements (WSN, EMCV and SARS2), or on red fluorescence measurements for PR8 using a Celigo cytometer.…”
Section: Methodsmentioning
confidence: 99%